Yeast GH30 Xylanase from Sugiyamaella lignohabitans Is a Glucuronoxylanase with Auxiliary Xylobiohydrolase Activity - Katarína Šuchová; Andrej Chyba; Zuzana Hegyi; Martin Rebroš; Vladimír Puchart (Molecules, 2022)
Xylanases are the enzymes that catalyze the breakdown of the main hemicellulose present in plant cell walls. They have attracted attention due to their biotechnological potential for the preparation of industrially interesting products from lignocellulose. While many xylanases have been characterized from bacteria and filamentous fungi, information on yeast xylanases is scarce and no yeast xylanase belonging to glycoside hydrolase (GH) family 30 has been described so far. Here, we cloned, expressed and characterized GH30 xylanase SlXyn30A from the yeast Sugiyamaella lignohabitans. The enzyme is active on glucuronoxylan (8.4 U/mg) and rhodymenan (linear β-1,4-1,3-xylan) (3.1 U/mg) while its activity on arabinoxylan is very low (0.03 U/mg). From glucuronoxylan SlXyn30A releases a series of acidic xylooligosaccharides of general formula MeGlcA2Xyln. These products, which are typical for GH30-specific glucuronoxylanases, are subsequently shortened at the non-reducing end, from which xylobiose moieties are liberated. Xylobiohydrolase activity was also observed during the hydrolysis of various xylooligosaccharides. SlXyn30A thus expands the group of glucuronoxylanases/xylobiohydrolases which has been hitherto represented only by several fungal GH30-7 members.